Anorexia nervosa - Lock, James (BMJ Publishing Group, 2009)
INTRODUCTION: Anorexia nervosa is characterised by a low body mass index (BMI), fear of gaining weight, denial of current low weight and its impact on health, and amenorrhoea. Estimated prevalence is highest in teenage girls, and up to 0.7% of this age group may be affected. While most people with anorexia nervosa recover completely or partially, about 5% die of the condition, and 20% develop a chronic eating disorder. Young women with anorexia nervosa are at increased risk of bone fractures later in life. METHODS AND OUTCOMES: We conducted a systematic review which aimed to answer the following clinical questions: What are the effects of treatments for anorexia nervosa? What are the effects of interventions to prevent or treat complications of anorexia nervosa? We searched: Medline, Embase, The Cochrane Library, and other important databases up to August 2007 (Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 40 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: anxiolytic drugs, cyproheptadine, inpatient/outpatient treatment setting, oestrogen treatment, psychotherapy, refeeding, selective serotonin reuptake inhibitors (SSRIs), and tricyclic antidepressants.